Kedudukan Bukti Digital dalam Sistem Peradilan Pidana Indonesia: Rekonsepsi Pengaturan dan Penguatan Chain of Custody di Era Cyber-Enabled Crime - Gilang Rizki Aji Putra (BULETIN ADALAH, 2024)
Digital transformation has reshaped criminal activity and positioned electronic evidence as a central element in criminal investigations. This article analyzes the juridical status of digital evidence within Indonesia’s criminal justice system, focusing on its legal basis, evidentiary value, and challenges related to authentication and the preservation of chain of custody. Using normative legal research with statutory, conceptual, and case approaches, the study finds that the Electronic Information and Transactions Law (ITE Law) has expanded the closed system of evidentiary instruments under the Criminal Procedure Code (KUHAP) by formally recognizing electronic information and documents as admissible evidence. Nevertheless, significant issues remain, including unclear substantive requirements for admissibility, the absence of comprehensive chain of custody standards, and disparities in law enforcement capacity. Court decisions demonstrate that evidentiary strength often depends on proving integrity and authenticity rather than clear normative standards. The article concludes that procedural reform, standardized digital forensic protocols, and institutional capacity building are essential. Keywords: Digital Evidence, Chain of Custody, Criminal Procedure Code (KUHAP), Electronic Information and Transactions Law (ITE Law), Digital Forensics.